A young woman's guide to sex - Voss, Jacqueline (Holt, 1987)
A comprehensive guide to sex and sexuality, especially for young women, with discussions of the male and female bodies, making decisions, pregnancy, masturbation, diseases, sexual responsibilities, desire, sexual problems, helpful organizations, homosexuality, and much more.